Correlation between particle deformation kinetics and polymer interdiffusion kinetics in drying latex films - Pohl, Katja (Langmuir : the ACS journal of surfaces and colloids, 2013)
Using an experimental setup which determines the turbidity of the sample and the efficiency of Förster resonance energy transfer (FRET) at the same time, we have correlated the particle deformation kinetics in a drying latex film, quantified by light scattering with the kinetics of polymer interdiffusion. Interdiffusion was quantified making use of energy transfer (FRET) between donor molecules and acceptor molecules, bound to polymer chains on different particles. When the chains cross the interparticle boundaries, the rate of energy transfer increases. The latex was prepared by miniemulsion polymerization. The amount of emulsifier employed during polymerization had a pronounced effect on the relative timing of interdiffusion and particle deformation. Increasing the amount of emulsifier delayed the onset of interdiffusion relative to the time when the film became transparent. This is mostly the consequence of a size effect, as opposed to surfactant acting as a barrier for transport